2020
DOI: 10.3390/molecules25051055
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Diphlorethohydroxycarmalol Isolated from Ishige okamurae Against Particulate Matter-Induced Skin Damage by Regulation of NF-κB, AP-1, and MAPKs Signaling Pathways In Vitro in Human Dermal Fibroblasts

Abstract: Particulate matters (PM), the main contributor to air pollution, have become a serious issue that threatens human’s health. Skin is the largest organ in humans, as well as the primary organ exposed to PM. Overexposure of PM induces skin damage. Diphlorethohydroxycarmalol (DPHC), an algal polyphenol with the potential of skin protection, has been isolated from the edible brown seaweed Ishige okamurae. The purpose of the present study is to investigate the protective effect of DPHC against PM (ERM-CZ100)-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Then, the intracellular ROS level and the viability of UVB-irradiated HDF cells were determined with the DCF-DA and the MTT assays, respectively [28]. In addition, the collagen synthesis level and the expression of MMPs were assessed with ELISA using the cell culture medium [28,35,36].…”
Section: In Vitro In Hdf Cellsmentioning
confidence: 99%
“…Then, the intracellular ROS level and the viability of UVB-irradiated HDF cells were determined with the DCF-DA and the MTT assays, respectively [28]. In addition, the collagen synthesis level and the expression of MMPs were assessed with ELISA using the cell culture medium [28,35,36].…”
Section: In Vitro In Hdf Cellsmentioning
confidence: 99%
“…Specifically, we reported, PM-exposed individuals were diagnosed with pulmonary neutrophilic inflammation and increased blood fibrinogen [32]. On the other hand, several studies suggested that compounds isolated from brown seaweeds are capable to inhibit UPM-induced inflammatory responses under in vivo and in vitro conditions [33,34]. Specifically, Wang et al…”
Section: Discussionmentioning
confidence: 89%
“…Seaweeds contain various bioactive compounds, such as polysaccharides, peptides, pigments, polyphenols, and sterols [8][9][10]. These bioactive compounds possess numerous health benefits, including antioxidant, anti-obesity, anti-cancer, anti-inflammatory, anti-melanogenesis, and UV protective effects [8,[11][12][13]. Recent research indicates that algae-derived compounds possess strong photoprotective effects [11,13].…”
Section: Introductionmentioning
confidence: 99%